Mangan Linjo “Kademangan Lingkungan Ijo” Upaya Menekan Angka Stunting dengan Budaya Konsumsi Sayur Organik di RW 04 RT 02 Kelurahan Kademangan Kota Probolinggo - Veronica Sri Astuti N. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2019)
Communities in Kademangan Village precisely in RW 04 RT 02, are still among those who are less concerned about healthy eating patterns. They still ignore the importance of the intake of nutrients needed by the body. Poor nutrition can lead to various health problems, one of which is stunting Stunting is a condition of growth failure in children (body and brain growth) due to malnutrition for a long time. Thus, children are shorter than normal children their age and have a delay in thinking. Malnutrition in a long time that occurs from the fetus in the womb until the beginning of the child's life (First 1000 Days of Birth). For this reason, community service activities by Panca Marga University Probolinggo 2019 KKN students are realized by realizing the